Quantifying the release of acidity and metals arising from drainage of acid sulfate soils in the Kelantan Plains, Malaysia - Enio, Mohd S.K. (Dnipro University of Technology, 2020)
Purpose. This paper discusses the release of acidity and toxic metals from acid sulfate soils in the Kelantan plains due to the oxidation of pyrite. Methods. A study was conducted in the field and laboratory using leaching column to quantify the release of acidity and metals from these acid sulfate soils. Findings. The highest pyrite content of 6.3% was recorded in the subsoil in the south region. Titrable actual acidity was significantly high (23.2 cmol H+ /kg) in soils of the southern part where jarosite occurred in the topsoil. Most of the acidity has been released at the beginning of the laboratory leaching experiment, indicating that in the real field situation, the oxidation of pyrite occurred immediately after the area was drained Originality. The depth at which pyrite layer occurs in the soils has important implication on land quality and crop production in the area. High amount of Al (0.36-0.81 cmolc/kg) and Fe (0.35-0.7 cmolc/kg) were found in the leachates. Practical implications. Opening an area of acid sulfate soils in the Kelantan Plains for agriculture had oxidized pyrite in the sediments, resulting in the release of high acidity and toxic level of Al, Fe and trace elements into the soils and waterways, which can affect crops and aquatic life. This is made worse by the release of As, B, Cu, Mn and Zn into the soil solution and waterways.